The Speed of Sound in Silk: Linking Material Performance to Biological Function. (6th June 2014) - Mortimer, Beth; Gordon, Shira D.; Holland, Chris; Siviour, Clive R.; Vollrath, Fritz; Windmill, James F. C.
<x xml:space="preserve">Abstract</x> Sonic properties of spider silks are measured independent of the web using laser vibrometry and ballistic impact providing insights into Nature's design of functionalized high‐performance materials. Through comparison to cocoon silk and other industrial fibers, we find that major ampullate silk has the largest wavespeed range of any known material. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>